BTB/POZ-zinc finger protein abrupt suppresses dendritic branching in a neuronal subtype-specific and dosage-dependent manner. - Li, W.; Wang, F.; Menut, L.; Gao, F.B. (Neuron, 2004)
How dendrites of different neuronal subtypes exhibit distinct branching patterns during development remains largely unknown. Here we report the mapping and identification of loss-of-function mutations in the abrupt (ab) gene that increased the number of dendritic branches of multiple dendritic (MD) sensory neurons in Drosophila embryos. Ab encodes an evolutionarily conserved transcription factor that contains a BTB/POZ domain and C2H2 zinc finger motifs. We show that ab has a cell-autonomous function in postmitotic neurons to limit dendritic branching. Ab and the homeodomain protein Cut are expressed in distinct but complementary subsets of MD neurons, and Ab functions in a transcriptional program that does not require Cut. Deleting one copy of ab or overexpressing ab had opposite effects on the formation of higher-order dendritic branches, suggesting that the Ab level in a specific neuron directly regulates dendritic complexity. These results demonstrate that dendritic branching can be suppressed by neuronal subtype-specific transcription factors in a cell-autonomous and dosage-dependent manner.